2015
DOI: 10.1177/1088868315586325
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Regulate Their Emotions? A Taxonomy of Motives in Emotion Regulation

Abstract: Emotion regulation involves the pursuit of desired emotional states (i.e., emotion goals) in the service of superordinate motives. The nature and consequences of emotion regulation, therefore, are likely to depend on the motives it is intended to serve. Nonetheless, limited attention has been devoted to studying what motivates emotion regulation. By mapping the potential benefits of emotion to key human motives, this review identifies key classes of motives in emotion regulation. The proposed taxonomy distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
585
1
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(674 citation statements)
references
References 179 publications
21
585
1
23
Order By: Relevance
“…This may seem to create some conceptual ambiguity because we are suggesting that the decision process should be considered a constitutive feature of empathy. Indeed, people can pursue a variety of goals that pertain to other emotional states such as anger, fear, and so forth; from an instrumental emotion regulation framework (Tamir, 2009(Tamir, , 2016, people have goals to pursue different emotions which will should implicate a similar, cybernetic decision logic (see also Gross, 2015;Moors et al, 2017). Given that similar goal selection processes can implicate in seemingly very different emotional outcomes (e.g., empathy, anger), it might seem counter-intuitive to posit that the goal selection process itself is a constitutive feature of empathy.…”
Section: Figure 2 Hierarchical Model Of Cybernetic Control (See Alsomentioning
confidence: 99%
See 1 more Smart Citation
“…This may seem to create some conceptual ambiguity because we are suggesting that the decision process should be considered a constitutive feature of empathy. Indeed, people can pursue a variety of goals that pertain to other emotional states such as anger, fear, and so forth; from an instrumental emotion regulation framework (Tamir, 2009(Tamir, , 2016, people have goals to pursue different emotions which will should implicate a similar, cybernetic decision logic (see also Gross, 2015;Moors et al, 2017). Given that similar goal selection processes can implicate in seemingly very different emotional outcomes (e.g., empathy, anger), it might seem counter-intuitive to posit that the goal selection process itself is a constitutive feature of empathy.…”
Section: Figure 2 Hierarchical Model Of Cybernetic Control (See Alsomentioning
confidence: 99%
“…When such approaches have been more specific, it has been in cataloguing different motivations (Zaki, 2014) and emotion regulation strategies (de Vignemont & Singer, 2006;Hodges & Biswas-Diener, 2007). For example, Zaki (2014) lists suffering, material costs, and interference with competition as motives that inhibit empathy, and positive affect, affiliation, and social desirability as motives that support empathy (for broader taxonomy of motives related to emotion regulation, see Tamir, 2016). While such a list is very useful in enumerating the ways that motivation matters, what these treatments leave unaddressed is how and why motivation maters and how competing motives are prioritized.…”
Section: Ends Of Empathy 20mentioning
confidence: 99%
“…Hedonic motives for emotion regulation follows the classical assumption that people will regulate their emotions in such a way to feel good and to avoid feeling bad (e.g., Larsen, 2000). Only recently have instrumental motives for emotion regulation been proposed (e.g., Tamir, 2009Tamir, , 2016Tamir et al, 2015;Tamir, Chui, & Gross, 2007). In this view, individuals are expected to prefer emotions that are perceived as useful, regardless of whether the emotion is pleasant or unpleasant (Tamir, 2016).…”
Section: Antecedents To Emotion Regulationmentioning
confidence: 99%
“…Only recently have instrumental motives for emotion regulation been proposed (e.g., Tamir, 2009Tamir, , 2016Tamir et al, 2015;Tamir, Chui, & Gross, 2007). In this view, individuals are expected to prefer emotions that are perceived as useful, regardless of whether the emotion is pleasant or unpleasant (Tamir, 2016). The perception of utility depends on emotion-outcome expectancies (Tamir et al, 2015).…”
Section: Antecedents To Emotion Regulationmentioning
confidence: 99%
“…Expressions of anger, frustration, pride, and appreciation can have adaptive functions for relationships within groups by strengthening social relationships and enhancing commitment and belonging, and the expression of some emotions may communicate to team members that their behavior is not acceptable and that corrections are required (Fischer & Manstead, 2008;von Scheve & Ismer, 2013). Accordingly, efforts to try to regulate a teammate's emotions may serve instrumental functions (Tamir, 2016) to reinforce behaviors among teammates intended to improve the team's performance. Qualitative research has found evidence that athletes regulated their own and others' emotions to improve the team's performance and to maintain teammate relationships (e.g., Tamminen & Crocker, 2013).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%